2014
DOI: 10.3892/etm.2014.1898
|View full text |Cite
|
Sign up to set email alerts
|

Urinary interleukin-18 as an early indicator to predict contrast-induced nephropathy in patients undergoing percutaneous coronary intervention

Abstract: Contrast-induced nephropathy (CIN) is at present the third leading cause of hospital-acquired acute kidney injury (AKI). Traditionally, it is diagnosed by measuring an increase of the serum creatinine (SCr) concentration. However, SCr is an insensitive marker for detecting CIN. This study was designed to investigate whether human urinary interleukin-18 (IL-18) is early predictive marker for CIN following coronary interventional procedures. The general clinical data of 180 patients who underwent coronary interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…It has been demonstrated that urinary neutrophil gelatinase‐associated lipocalin (NGAL; AUC = 0.96) and kidney injury molecule type 1 (KIM‐1; AUC = 0.71), performed better than liver fatty acid‐binding protein (L‐FABP; AUC = 0.64) assessed at 12 h following coronary angiography in the prediction of contrast‐induced nephropathy . Accordingly, urinary interleukin‐18 assessed at 6 h following CA/PCI has been shown to herald the onset of CI‐AKI (AUC = 0.81) . Although the aforementioned biomarkers exhibited higher predictive power towards CI‐AKI prediction than urinary renalase in our study, the application of different definitions of CI‐AKI in diverse populations precludes direct comparison of the results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that urinary neutrophil gelatinase‐associated lipocalin (NGAL; AUC = 0.96) and kidney injury molecule type 1 (KIM‐1; AUC = 0.71), performed better than liver fatty acid‐binding protein (L‐FABP; AUC = 0.64) assessed at 12 h following coronary angiography in the prediction of contrast‐induced nephropathy . Accordingly, urinary interleukin‐18 assessed at 6 h following CA/PCI has been shown to herald the onset of CI‐AKI (AUC = 0.81) . Although the aforementioned biomarkers exhibited higher predictive power towards CI‐AKI prediction than urinary renalase in our study, the application of different definitions of CI‐AKI in diverse populations precludes direct comparison of the results.…”
Section: Discussionmentioning
confidence: 99%
“…He et al 122 carried out a study on 180 patients who underwent coronary interventional procedures at the Department of Cardiology. Urine IL-18 levels were found to be increased in the CI-AKI patients 6-12 hours after the CM injection, compared with those in the non-CI-AKI patients (P<0.01).…”
mentioning
confidence: 99%
“…Ling et al delivered preliminary evidence that urinary IL‐18 assessed at 24 h accurately identified patients at risk of CI‐AKI. This fact was later corroborated on 180 participants by He et al, who found that IL‐18 assayed at 12 h accurately selected subjects at risk of CI‐AKI (AUC = 0.81). Although urinary IL‐18 was higher in CI‐AKI than non‐CI‐AKI group at 6 h, only at 12 h did it reach statistical significance in ROC curve analysis.…”
Section: Discussionmentioning
confidence: 55%
“…Large body of evidence supports the use of urinary neutrophil gelatinase‐associated lipocalin (NGAL), however, little is known about the efficacy of other potential urinary biomarkers as an early CI‐AKI biomarkers, especially in the setting of patients with preserved baseline kidney function. Urinary interleukin 18 (IL‐18), kidney injury molecule type 1 (KIM‐1), and liver fatty acid‐binding protein (L‐FABP) have been so far evaluated as potential disease markers, but to date none of the studies has unequivocally proved the superiority of a single marker for CI‐AKI prediction.…”
Section: Introductionmentioning
confidence: 99%